2000
DOI: 10.1109/94.891991
|View full text |Cite
|
Sign up to set email alerts
|

Investigating dc polyethylene threshold by space charge. Current and electroluminescence measurements

Abstract: It has been proposed recently [l] that the lowest level of dc field, above which electrical degradation may occur, is associated with the formation of space charges in insulation. Therefore, inference of field levels above which space charge accumulates in a given material may provide fundamental information for material characterization and system design. Threshold field values were estimated through evidence of space charge accumulation derived from conduction current, space charge amplitude and electrolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Electrodes were made of semicon (high voltage, anode) and aluminium (cathode). Tests with gold electrodes prepared by cold sputtering were also performed [3,4]. Electroluminescence was detected through a photomultiplier (PM) working in photon counting mode, using specimens metallized on both surfaces with semitransparent layers of gold deposited by cold sputtering.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrodes were made of semicon (high voltage, anode) and aluminium (cathode). Tests with gold electrodes prepared by cold sputtering were also performed [3,4]. Electroluminescence was detected through a photomultiplier (PM) working in photon counting mode, using specimens metallized on both surfaces with semitransparent layers of gold deposited by cold sputtering.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure adopted to measure EL during depolarization was slightly different. We have already reported that under short-circuit conditions, the EL is a transient process occurring immediately after grounding the sample [4]. The analysis of the EL decay necessitates a shorter sampling time which has been chosen at 10 ms. Voltage was applied to the specimen by using a high voltage switch which can be used to ground the sample after the polarization time.…”
mentioning
confidence: 99%
“…However, this value is significantly lower than the value of 10 kV/mm mentioned in literature for polyethylene. 5,6 As the blocking layer was fluorinated polyethylene, its dielectric properties such as permittivity and conductivity are different from the normal one; therefore, it is possible the charges accumulated at the interface between the two layers may be related to the Maxwell-Wagner polarisation.…”
Section: And Lisheng Zhongmentioning
confidence: 99%
“…The injection of charge carriers occurs at the conductor/solid insulator interface when the applied electric field is higher than the threshold field for the specific dielectric material. For example, the threshold for PE is about 10 kV/mm [88]- [90]. The injected charge carriers are expected to have the same polarity of the related electrode, i.e., positive charges are injected from the anode, and negative charges are injected from cathode, which is called homo-charges.…”
Section: B Space Charge Effects In Hvdc Cablesmentioning
confidence: 99%